2021
DOI: 10.3389/fonc.2021.741737
|View full text |Cite|
|
Sign up to set email alerts
|

Survival Outcomes After Breast-Conserving Therapy Compared With Mastectomy for Patients With Early-Stage Invasive Micropapillary Carcinoma of the Breast: A SEER Population-Based Study

Abstract: BackgroundInvasive micropapillary breast carcinoma (IMPC) is a relatively rare pathological type of invasive breast cancer. Little is currently known on the efficacy and safety of breast-conserving treatment (BCT, lumpectomy plus postsurgical radiation) compared with mastectomy in women diagnosed with early-stage IMPC. Accordingly, we sought to investigate the long-term prognostic differences between BCT and mastectomy in patients with T1-3N0-3M0 invasive micropapillary breast carcinoma using data from the Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Meanwhile, a previous finding also demonstrated that the survival outcomes of patients with early-stage IMPC who underwent breast-conserving surgery were not inferior to those with mastectomy. 12 Moreover, we confirmed that patients with IMPC benefited significantly from radiotherapy in terms of both OS and BCSS, an issue that has long been controversial. 26 27 Additionally, consistent with a previous study, chemotherapy was inappropriate for use as a predictor for BCSS after adjustment for other factors.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Meanwhile, a previous finding also demonstrated that the survival outcomes of patients with early-stage IMPC who underwent breast-conserving surgery were not inferior to those with mastectomy. 12 Moreover, we confirmed that patients with IMPC benefited significantly from radiotherapy in terms of both OS and BCSS, an issue that has long been controversial. 26 27 Additionally, consistent with a previous study, chemotherapy was inappropriate for use as a predictor for BCSS after adjustment for other factors.…”
Section: Discussionsupporting
confidence: 67%
“…8 In addition to the factors included in the tumor-node-metastasis classification, evidence indicates that other elements, such as demographic characteristics and treatment strategies, impact the prognosis of patients with IMPC. [9][10][11][12] Therefore, it is important to…”
Section: Introductionmentioning
confidence: 99%
“…Pathologists have described IMPC lesions as having an inside-out reversed polarity pattern with a typical cuticle-like microvillous secretory surface facing the stroma, resulting in a gap between the stroma and the neoplastic epithelial cells (4). Prior studies have demonstrated that as an aggressive variant, IMPC is linked to a larger tumor size, more advanced Tumor, Node, Metastasis (TNM) staging, a greater proportion of nodal involvement, and a higher degree of lymphovascular invasion (LVI); these characteristics can contribute to a high early recurrence rate and a poorer prognosis (5).…”
Section: Introductionmentioning
confidence: 99%
“…In both species, surgery and chemotherapy are the most common standard treatments for breast cancer, as well as hormonal and target therapies available for human patients. However, depending on the patient's clinical staging, satisfactory therapeutic results for invasive micropapillary carcinoma are a challenge due to its high capacity of invasion and metastasis ( 24 26 ).…”
Section: Introductionmentioning
confidence: 99%